Transforming the World in Which We Live: Laureate's Transnational Civic Learning Project - William M. Plater (Laureate Education Inc, 2017)
Higher education serves as an agent of social change that plays a significant role in the development of socially conscious and engaged students. The duty higher education has toward society, the role for-profit educational institutions play in enhancing the public good, and the prospect of making social change an element of these providers' missions are discussed. Laureate's Global Citizenship Project is introduced, highlighting the development of the project's civic engagement rubric and the challenges of assessing civic engagement.